Problematika Pemanfaatan Media Pembelajaran Berbasis TIK di Madrasah Ibtidaiyah - Nila Nimatul Lailiyah; Shibi Zuharoul Mardliyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
Islamic Education (PAI) was one of the method to give the Islamic values toward students. It was very important to be taught among the students that without any compulsions and who had high interest. The usage of learning medium was one of the effort in stimulating the students' interest. But, from this aim, there were some obstacles among the teachers in implementation, particularly the ICT based, moreover in the pandemic Covid-19 that force the students to learn